Eco-friendly paper-based colorimetric sensor for portable and rapid detection of lead (II) ions in aqueous environment - N. M. Poovadichalil (22927906) (2025)
Lead contamination in water bodies poses significant environmental and health risks, necessitating effective detection methods. This study presents a novel, cost-effective, and portable paper-based sensor for the visual detection of lead (II) ions in an aqueous medium using the colorimetric dyes Eriochrome Black T and Bromothymol Blue. The sensor's sensitivity to varying concentrations of lead (II) ions is explored using UV–visible spectroscopy, with pH-adjusted dye solutions in acidic, neutral, and basic conditions. Both Eriochrome Black T and Bromothymol Blue dyes exhibited distinct colorimetric responses to the presence of lead (II), with optimal detection occurring in neutral pH environment. A concentration range of 60–140 ppm of lead (II) ions was examined, and the detection limits were lowest for Bromothymol Blue dye, found to be around 6 ppm. Furthermore, the selectivity of the dyes was tested against other metal ions, showing high specificity for lead (II) ions. The sensor's stability was verified across a temperature range of 25–90 °C. Finally, a paper-based chemo sensor was fabricated to demonstrate the sensor's real-time applicability, where visual color changes confirmed lead (II) detection in water. The developed sensor offers a promising alternative for field-based detection of lead in contaminated water sources, providing a low-cost, easy-to-use, and reliable method for environmental monitoring. Other Information Published in: International Journal of Environmental Science and Technology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13762-025-06636-6